UPAYA MENINGKATKAN KOMUNIKASI ANTAR PRIBADI SISWA MELALUI KONSELING TEMAN SEBAYA SISWA KELAS XI SEMESTER GENAP DI SMK GAJAH MADA BANDAR LAMPUNG - Diswantika, Noviana; Hisbullah, Ahmad (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem that occurs in this study is the lack of interpersonal communication skills of students, which causes students to be inferior and ashamed to give their opinions due to lack of interpersonal communication. At the same time, peer counseling services are an alternative to solving students' problems with how to communicate with students privately. The purpose of this research is to improve interpersonal communication through peer counseling services. This research uses a qualitative approach with a guidance and counseling action research design (PTBK). For data collection, researchers used observations and interviews and used a questionnaire, which was then analyzed to obtain conclusions. Based on observations during the provision of peer counseling services cycle 1 to cycle two is done, an increase in interpersonal communication skills of students by 0.33 points or 10% from the period I to cycle II. So it can be concluded that the peer counseling service has succeeded in improving personal communication among students of SMK Gajah Mada Bandar Lampung.